Geochemistry, groundwater and pollution - Appelo, C. A. J | Postma, D. (A.A.Balkema / Paises Bajos, 2005)
Groundwater geochemistry is an intersisciplinary science that relates the quality of groundwater to various processes and reactions in the subsurface environment. Pollution and increased exploitation of groundwater resources have demanded for an improved understanding of the concentration limits and variations of solute ions and chemistry